IJABE has successfully been covered and indexed in Thomson Reuter’s SCI - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2014)
I received a formal letter in late July which was signed by Marian Hollingsworth, the Publisher Relations Director of Thomson Reuters, which confirmed that the International Journal of Agricultural and Biological Engineering (IJABE) has been selected for complete coverage in Thomson Reuter’s products and services. Beginning with V. 6(1) 2013, IJABE will be indexed and abstracted in: ♦ Science Citation Index Expanded (also known as SciSearch®) ♦ Journal Citation Reports/Science Edition ♦ Current Contents®/Agriculture, Biology, and Environmental Sciences ♦ Biological Abstracts ♦ BIOSIS Previews I am very pleased to announce this major milestone of IJABE’s coverage in Thomson Reuters’s five products and indexing services. IJABE has become the first SCI-indexed journal of its kind in China, which is a major confirmation of the successful establishment of the journal. The first official IJABE Impact Factor will be published in the 2015 Journal Citation Reports, which will be yet another major marker of the success of the journal. It is also a clear indicator of the success of the open access model, as I mentioned in the article entitled “Open access leads to success” published in the first issue of IJABE in 2014.